Experimental Study on the Degree of Surface Generation by Edge Preparation Tools in Milling 316L - Ibrahim, Rasidi; Yee Long, Chong; Yung Ng, Chee; Hakim Rafai, Noor; Sukri Mustapa, Mohammad; Ismail, Al Emran (International Journal of Engineering and Technology, 2019)
Milling is one of the most common machining methods in the industry today to produce the desire shape from raw workpiece. Improvement of milling performance is always the simplest way to reduce the production cost and increase the productâ€™s quality. Since cutting tool is the basic requirement of a milling process, the study on structure of cutting tool especially the cutting edge is a breakthrough point to enhance the milling performance.Â  Geometry of cutting edge of uncoated endmill with diameter of 6mm had been modified through edge preparation process in this study. The cutting radius had been enlarged and the roughness on cutting edge is smoother after the preparation process. The second method to improve milling performance in this study is utilization of cutting fluid. Besides conventional flood cutting, Minimal Quantity Lubrication (MQL) is another method to provide lubrication and reduce cutting temperature by coolant in â€œmistâ€ form. In this study, both cutting edge preparation and MQL methods are applied in side milling as well as slot milling. The chosen material for the workpiece was stainless steel, a metal with non-magnetic and high corrosion resistance characteristics. The milling performance was evaluated by cutting force and machined surface roughness, which are measured by dynamometer and roughness tester respectively. The lowest cutting force with 93.23N as well as lowest side surface roughness of 0.42Î¼m in slot milling was observed under MQL condition with edge prepared tool.Â Â